Analysis and prospect of communication technology in smart urban rail - Junhui ZHAO; Danyang ZHANG; Lin HE (Dianxin kexue)
The particularity of the urban rail transit environment leads to the problems such as reducing communication reliability, delay performance and operating efficiency bottlenecks.Therefore, the demand for urban rail communication was analyzed from the perspective of overall operational efficiency.New intelligent communication control technologies such as T2T (train to train) communication, 5G, artificial intelligence, and mobile edge computing were combined to summarize and prospect the key technologies of urban rail communication.Then, a new type of urban rail communication network architecture was proposed.Finally, the research direction and challenges of smart urban rail communication technology were discussed, which also provided a research foundation for the development of smart cities.